Synthesis of thiol-terminated PEG-functionalized POSS cross-linkers and fabrication of high-strength and hydrolytic degradable hybrid hydrogels in aqueous phase. (July 2019) - Li, Heling; Dai, Jinchi; Xu, Qi; Lu, Cuifen; Yang, Guichun; Wang, Feiyi; Nie, Junqi; Hu, Xingjian; Dong, Nianguo; Shi, Jiawei
Graphical abstract: Highlights: High-strength and hydrolytic degradable POSS-PEG hybrid hydrogels were fabricated. The cross-linkers were prepared by linking hydrophilic PEG onto hydrophobic POSS. All the prepared hybrid hydrogels were achieved with high mechanical strength. All the hybrid hydrogels had good cell compatibility. Abstract: A series of high-strength and hydrolytic degradable POSS-PEG hybrid hydrogels were successfully fabricated by Michael addition reaction of 4-arm-PEG-maleimide with thiol-terminated PEG-functionalized POSS cross-linkers in aqueous phase. The cross-linkers, which are hydrophilic, multifunctional and contain esters, were prepared by linking hydrophilic PEG with different chain length onto hydrophobic POSS and terminating with a thiol group. All the prepared hybrid hydrogels were achieved with a porous structure and high mechanical strength, and the G′ of POSS-PEG500 hybrid hydrogel reached a maximum of 15, 000 Pa, which is much higher than our previous POSS-PEG hybrid hydrogels prepared by monofunctional POSS. The swelling ratio and hydrolytic degradation rate of hybrid hydrogels increased with the increase of PEG chain length. In vitro cell culture showed that all the hybrid hydrogels had good biocompatibility. Thus, these hybrid hydrogels exhibited the potential for tissue engineering scaffolds.